QUALITY OF STUDENTS’ MATHEMATICAL CONCEPT UNDERSTANDING INSTRUMENTS USING THE RASCH MODEL (Proceedings of the International Conference on Future of Education, 2024)
This study aims to describe the quality of the questions on students' ability to understand mathematical concepts from the aspects of validity, reliability, level of difficulty of the questions, and the distinguishing power of the items. The data obtained is the end of semester assessment data for class XII with the documentation method in the form of 15 multiple choice questions and tested on 29 vocational students. Data were analyzed using a modern modeling approach, namely the Rasch Model using Ministep software. The results of the analysis obtained in this study are the quality of questions from the validity aspect obtained 13 questions in the valid category and 2 questions in the invalid category. The Cronbach alpha (KR-20) reliability value is 0.57 (medium) with a person reliability value of 0.59 (weak) and a question item reliability value of 0.84 (good). The average difficulty index of the items shows that there are four categories of item difficulty, namely 3 very easy questions, 3 easy questions, 7 difficult questions, and 2 very difficult questions. The differentiating power of the items using Rasch modeling obtained a differentiating power value of 3.34 and 1.76 in the sufficient category, which means that the questions made are sufficient to distinguish students who are able to answer questions and students who have low ability to answer questions. Based on this, the research instrument developed can be used to measure students' mathematical concept understanding ability.
Keywords: Understanding of Mathematical Concepts; Rasch Model; Ministep; Item Response Theory